Comparison of PLA-Based Micelles and Microspheres as Carriers of Epothilone B and Rapamycin. The Effect of Delivery System and Polymer Composition on Drug Release and Cytotoxicity against MDA-MB-231 Breast Cancer Cells - Katarzyna Jelonek; Alicja Zajdel; Adam Wilczok; Bożena Kaczmarczyk; Monika Musiał-Kulik; Anna Hercog; Aleksander Foryś; Małgorzata Pastusiak; Janusz Kasperczyk (MDPI AG, 2021)
Co-delivery of epothilone B (EpoB) and rapamycin (Rap) increases cytotoxicity against various kinds of cancers. However, the current challenge is to develop a drug delivery system (DDS) for the simultaneous delivery and release of these two drugs. Additionally, it is important to understand the release mechanism, as well as the factors that affect drug release, in order to tailor this process. The aim of this study was to analyze PLA-PEG micelles along with several types of microspheres obtained from PLA or a mixture of PLA and PLA-PEG as carriers of EpoB and Rap for their drug release properties and cytotoxicity against breast cancer cells. The study showed that the release process of EpoB and Rap from a PLA-based injectable delivery systems depends on the type of DDS, morphology, and polymeric composition (PLA to PLA-PEG ratio). These factors also affect the biological activity of the DDS, because the cytotoxic effect of the drugs against MDA-MB-231 cells depends on the release rate. The release process from all kinds of DDS was well-characterized by the Peppas-Sahlin model and was mainly controlled by Fickian diffusion. The conducted analysis allowed also for the selection of PLA 50/PLA-PEG 50 microspheres and PLA-PEG micelles as a promising co-delivery system of EpoB and Rap.